The Politics of Muslim Identities in Asia - Ahmad, Irfan; Bahrawi, Nazry; Hasyim, Syafiq; Imad Alatas, Syed; Islam, Imrul; Lumina, Iulia; Lumina, Iulia; Mohsina, Nazneen; Nelson, Matthew J.; Quimpo, Nathan Gilbert; Smith Finley, Joanne (Edinburgh University Press, 2022)
Explores the intersection between Islam and politics in contemporary Southeast Asia, South Asia and ChinaGives a comparative view of Asia’s diverse Muslim identities, looking at the complexity of identity politics and the instrumentalisation of religious difference that create social dividesSituates the contemporary contestations of identity and belonging amid new waves of Islamic revivalism, ethnic nationalism and political repressionIncludes 9 country-based case studies: Singapore, Malaysia, Pakistan, Indonesia, Bangladesh, Philippines, India, Myanmar and ChinaFeatures contributions from experts in political science, anthropology, Islamic studies, sociology including: Irfan Ahmad, Syed Imad Alatas, Nazry Bahrawi, Syafiq Hasyim, Imrul Islam, Nazneen Mohsina, Matthew J. Nelson, Nathan Gilbert Quimpo and Joanne Smith Finley Approaching religious identity with an emphasis on agency and contestation, this book offers a historical perspective on the development of Muslim identities in Asia. It examines the contingent politics that influence how Muslims constitute themselves as modern subjects. Through 9 country-based case studies, the book analyses how Muslims articulate their religious identity vis-à-vis the state and society in which they live, and how their position relates to specific social and political contexts. The contributors survey how religious affiliation sparks a politics of difference in contexts where Islamic practices, beliefs and aspirations are contested, as well as where Muslims are framed as the ‘Other’